Evaluation of the fundamentals of pedagogical activity professional development programme for teachers (2016–2023) - Margeviča-Grinberga, Ieva; Kiris, Kaspars; Lanka, Ērika; Ābele, Rita (Frontiers in Education, 2025)
The Latvian education system is facing a severe teacher shortage due to causes such as an ageing teaching workforce, high workloads, inadequate salaries and the impact of the COVID-19 pandemic. To help address the lack of trained teachers, a specialised professional development programme of 72 academic hours, Fundamentals of Pedagogical Activity, has been implemented. The initiative aims to provide individuals with professional skills the chance to engage in teaching activities across general, vocational, and interest-based education sectors. This study, conducted from 2016 to 2023, sought to evaluate the programme’s effect on participants’ development of professional skills and their motivation to pursue a career in teaching. The research uses a descriptive method approach with questionnaires and focus group discussions explores participants’ motivations for enrolling in the programme and the effect on their professional development. Fundamentals of Pedagogical Activity participants expressed strong interest in improving teaching skills and obtaining a teaching certificate in order to pursue significant career progress and continued professional growth after finishing the programme.